Application of economic and regulatory instruments for emission management : a case study of diesel and electric tempos in Kathmandu city - Rai, Babu Ram; Nurul Amin, A.T.M.; Morishita, Hideharu; Thapa, Gopal B.; Nepal Oil Corporation, Kathmandu; Canadian International Development Agency (CIDA); Canadian Universities Consortium (CUC) (Bangkok : Asian Institute of Technology, 1999)
Metro Kathmandu is facing the menacing problem of vehicular emission, which poses a serious environmental problem. Vehicular emission particularly originates more from diesel Tempos (three wheeler vehicles). It is one of the major causes of the air pollution in the Metro. Absence of land use planning, poor vehicle maintenance, weak enforcement of regulatory measures, low fuel quality, and import of old vehicles are known to be the other major sources of vehicular emission. This study focuses on the scope of greater use of regulatory and economic instruments to abate the emission for improving the air quality of Kathmandu and thereby contributing to urban environmental management of the city. - An increase of urban population is a major cause of massive growth of vehicles in the city. The urban population of the Metro was 150,402 in 1971 and it rose to 235,160 in 1981. By 1991, the population soared to 421,258. As a result, the demand for transportation services have increased rapidly. One response to this demand has been increased of Tempos in the city as source of cheap transportation services. But that this cheap service is taking place at an environmental costs is not commonly understood by all involved .. Also, most of these vehicles use diesel as their fuels and most diesel Tempo drivers have old vehicles. These are plying creating more pollution in the Metro. Yet, almost no diesel Tempo owners and drivers are willing to pay environmental or pollution charges. In the absence of proper economic and regulatory instruments' applications, this situation remains unchanged. Conversion of diesel Tempos into electric vehicles is highly desirable to manage the problem of emission in Kathmandu. One barrier to doing this is the high cost of conversion DVs to EVs. The regulatory and economic instruments have been studied for this research from the above issues in view. Most people would like to see reduction of emission even by banning of the Tempos. However, once they take by apply them of the regulatory and economic measures in view, these instruments appreciate their role to contain pollution. They have suggested that the government should provide subsidy, tax incentives and softloan for the environmentally friendly electric vehicles' operations and promotions. These highly preferred vehicles, however, are not getting produced now in sufficient number due to high initial investment and operating costs. The government had already planned to provide softloan to the battery charging operators. However, it was not acted properly until January 1999. Making emission standard compulsory and strict enforcement are required for non complying vehicles with the provision of higher emission charges and registration fees for high polluting vehicles. The government should provide incentives and subsidies for EV operations and promotions, specifically the government should provide softloan for conversion ofDVs into EVs.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science. School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1999
Keywords: Diesel motor exhaust gas -- Nepal -- Kathmandu